PEMANFAATAN APLIKASI AUDACITY PADA PEMBELAJARAN ISTIMĀ’ UNTUK MADRASAH IBTIDAIYYAH NEGERI SATU SUNGAI TARAB - Amrina, Amrina; Rezi, Melisa; Mudinillah, Adam; Geofani, Chintia; Hikmah, Durrotul (STIQ Amuntai, 2022)
This study aims to describe the use of learning media that supports exceptional learning in. The application used is the Audacity application. The Audacity application is designed to create audio-based learning media and is very suitable for special learning. The treatment of the Audacity application at Madrasah Ibtidayyah Negeri 1 Sungai Tarab, namely Maharah learning. This study uses qualitative research methods that are literature study and small observations in schools. The sources of this research are national and international journals, as well as books with the same title as this research. The results of this study explain that Audacity can be used by students in special learning and students can practice it directly so that they can add sounds, reduce sounds, and combine sounds, while the benefits of the Audacity application for educators are that it will be easier to deliver special subject matter. Furthermore, students are no longer confused with Arabic letters because they are by the original reading (Arabic Language). Therefore, it is hoped that other schools can use this application so that it can be in special learning.Keywords: Audacity, Istima’, Ibtidaiyyah